Factors Affecting Financial Performance with Capital Structure as Intervening Variables in Pharmaceutical Companies Listed on the IDX - Fadhlan Fachri; M. Irsan Nasution; Renny Maisyarah (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to find out whether company size and liquidity have a significant effect on financial performance by going through capital structure as an intervening variable in pharmaceutical companies listed on the IDX. The data used is the annual report of each company, which is published through the www.idnfinancials.com website. The research method used in this study is the associative method. The sampling method used is puposive sampling with a total sample of 6 pharmaceutical companies listed on the Indonesia Stock Exchange and data from 2018 – 2024. The results of this study show that company size has a significant effect on profitability in pharmaceutical companies listed on the IDX. Liquidity has a significant effect on profitability in Pharmaceutical Companies listed on the IDX. The size of the company does not have a significant effect on the capital structure of pharmaceutical companies listed on the IDX. Liquidity has a significant effect on the capital structure of pharmaceutical companies listed on the IDX. Profitability does not have a significant effect on the capital structure of pharmaceutical companies listed on the IDX. Feasibility does not function as an intervening variable between the size of the company and the capital structure of pharmaceutical companies listed on the IDX. Profitability functions as an intervening variable between liquidity and capital structure in pharmaceutical companies listed on the IDX.